Fracture toughness resistance curves for a delamination in CFRP MD laminate composites, Part I: Nearly mode II deformation. (June 2022) - Mega, Mor; Dolev, Orly; Banks-Sills, Leslie
Abstract: In this investigation nearly mode II initiation and resistance energy release rate values, required for delamination propagation, were determined based on quasi-static calibrated end loaded split (C-ELS) fracture tests. Two multi-directional (MD) carbon fiber reinforced polymer (CFRP) material systems were examined. The first was manufactured as a wet-layup, with an initial delamination between a unidirectional ply and a plain woven ply. The second was manufactured from a prepreg, with an initial delamination along an interface between two plain woven plies oriented differently. Two-dimensional finite element analyses (FEAs) of the tested specimens were performed. Based upon the FEA results, with use of the displacement extrapolation (DE) method, as well as the virtual crack closure technique (VCCT), stress intensity factors were calculated. The obtained values were used to determine the in-plane mixed-mode phase angle for each test, which indicated nearly mode II deformation. Fracture toughness resistance curves or R -curves were generated as a function of the delamination extension. The critical initiation and resistance energy release rate values were obtained from the stress intensity factors, as well as with the J -integral, which are local methods. In addition, the global experimental compliance method (ECM) was used. Small differences were observed between the results obtained by means of the two methods. From a comparison between the R -curves of the two material systems, it was seen that the initiation energy release rate values were higher for the prepreg by 25.5%. A greater difference was found in the increasing portion of the R -curves, as well as the steady state energy release rate values. Highlights: Nearly mode II C-ELS fracture toughness resistance tests were carried out. Two composite multidirectional laminate material systems were compared. Two analysis methods, global and local were employed and compared. Resistance curves were fitted to the test results for each material system. The mode mixity for the tested MD interfaces was evaluated.